A prospective study on association between comprehensive lifestyle scores and cognitive function changes in community-dwelling older adults in Tianjin city - Muya ZHANG; Xian CAI; Liping ZU; Huichao ZHAO; Tianyu WANG; Chenyu LI; Jing YUAN; Fei MA (Zhongguo gonggong weisheng)
ObjectiveTo investigate the association between comprehensive lifestyle scores and changes in cognitive function among community-dwelling older adults in Tianjin city. MethodsA prospective cohort study was conducted. From March to April 2016, eldly adults aged 65 years and above were recruited as research subjects in Tianjin through multi-stage cluster random sampling. Baseline data collection included basic demographic characteristics, lifestyle habits, and health status. A comprehensive lifestyle score was constructed based on overweight or obesity, physical activity, smoking, alcohol consumption, diet, and sleep. Scores of 0 – 1 were defined as unhealthy lifestyle, 2 – 4 as average lifestyle, and 5 – 6 as healthy lifestyle. Annual follow-ups were conducted from 2017 to 2019. Cognitive function was assessed using the Wechsler Adult Intelligence Scale (Chinese revised edition). Generalized estimating equations were used to analyze the association between different lifestyle groups and changes in cognitive function. ResultsA total of 816 participants were included, with an average age of (76.60 ± 9.46) years. Generalized estimating equation analysis showed that, compared with a healthy lifestyle, an unhealthy lifestyle was statistically associated with lower scores in full-scale intelligence quotient (β = – 2.839), verbal intelligence quotient (β = – 2.438), performance intelligence quotient (β = – 2.987), comprehension (β = – 1.260), digit symbol (β = – 2.372), block design (β = – 1.592), and object assembly (β = – 1.974) (all P < 0.05). ConclusionsAn unhealthy lifestyle is associated with cognitive decline among older adults in a community in Tianjin city. Adhering to a healthy lifestyle may reduce the risk of cognitive decline.